Review of Theories Explaining Tax Compliance Behaviour - Bhattarai, Toya N.; Upreti, Surendra Kumar; Kadel, Madan (Molung Educational Frontier, 2026)
Tax compliance remains a complex and often unattainable objective for many tax administrations, despite being a crucial component of public finance and governance. The study examines how taxpayer decisions are influenced by both non-economic (such as moral values, social norms, perceived fairness, and institutional trust) and economic (such as audit probability and penalties) factors using a qualitative literature survey method. Five main theoretical models—the Economic Deterrence Model, Socio-Psychological Theory, Fiscal Exchange Theory, Comparative Treatment Model, and Political Legitimacy Model—that explain tax compliance behaviour are thoroughly reviewed and synthesized in this study. The review’s main conclusion is that there is not a single theory that adequately accounts for the variety of reasons people have for complying with tax laws. Instead, an integrated approach that considers the interplay between voluntary, value based motivations and enforcement mechanisms is necessary to gain a thorough understanding of taxpayer behaviour. The findings of this study reveal that creating efficient tax systems requires taking into account deterrence tactics as well as initiatives to promote equity, openness, and political legitimacy in government.